Antibacterial poly (ethylene glycol) diacrylate/chitosan hydrogels enhance mechanical adhesiveness and promote skin regeneration. (1st December 2019) - Huang, Lin; Zhu, Ziyu; Wu, Dongwei; Gan, Weidong; Zhu, Shanshan; Li, Wenqiang; Tian, Jinhuan; Li, Lihua; Zhou, Changren; Lu, Lu
Highlights: PEGDA/CS and PEGDA/TCS DN hydrogels were prepared by a simple soaking strategy. The DN hydrogels displayed better mechanical properties and tissue adhesiveness. The hydrogel shows good active substance loading and sustained release properties. They promotes wound healing by anti-inflammatory and promoting neovascularization. Abstract: Various functional active hydrogels have been widely applied in tissue regeneration, especially in fields of wound repair as they are similar to the natural extracellular matrix (ECM) and can maintain moist at the wound site. However, preparing a hydrogel with multifunctional properties including high mechanical properties, excellent biocompatibility and long-term antibacterial activity is still a challenge. Herein, we developed a series of double network hydrogels based on poly (ethylene glycol) diacrylate (PEGDA) and chitosan (CS) or thiolated chitosan (TCS). The hydrogels presented in situ forming properties, good mechanical strength, adhesiveness, antibacterial activity and biocompatibility. The sample with the optimal formula of 15 wt% of PEGDA and 2 wt% of CS or TCS showed excellent mechanical adhesiveness, sustained release of antibacterial peptide and plasmid DNA, and it significantly accelerated in vivo wound healing process in a full-thickness skin defect model by reducing the inflammation and promoting the angiogenesis, meaning that the prepared hydrogels are excellent candidates for wound dressing.